Dental instruments : a pocket guide - Bartolomucci Boyd, Linda R. (St. Louis, MO : Saunders Elsevier, 2009)
From the Publisher: Confidently recognize and manage dental instruments with this innovative, visually detailed resource. Dental Instruments: A Pocket Guide pairs thorough descriptions of more than 300 instruments with high-quality photographs and illustrations for accurate, efficient identification. The book's unique flashcard-style format helps you review instruments and gauge your knowledge, while its spiral-bound design gives you fast, easy access to procedural support, making this convenient guide ideal for both studying and on-the-job reference. More than 450 high-quality photographs and illustrations depict instruments in both full detail and individual components for quick, easy identification. The convenient pocket-sized, spiral-bound design makes it easy to access information at a glance and in any setting. The unique, full-color, flashcard-style format helps you test your retention and understanding. Dedicated coverage of dental specialties provides quick reference to specific tools you'll need for procedures in endodontics, orthodontics, periodontics, and oral surgery. A companion Evolve website enables you to apply what you've learned with interactive drag-and-drop tray setup exercises and verify your knowledge through self-assessment quizzes. 3 new chapters familiarize you with preventive instruments and bleaching trays, dental materials equipment, and radiography equipment. 20 additional orthodontic instruments keep you up-to-date with the latest tools in orthodontic practice. New tray setup images demonstrate proper instrument arrangement for 24 common procedures, including 9 new to this edition. Practice Notes now provide helpful usage tips and guidelines for every instrument. Sterilization Notes present proper procedures for sterilizing or discarding each instrument. More than 100 Instruments In Use photographs visually enhance your understanding of instrument use with patients.
1. Basic dental instruments -- 2. Enamel cutting instruments -- 3. Local anesthetic syringe and components -- 4. Evacuation devices and air/water syringe tip -- 5. Dental handpieces -- 6. Burs and rotary attachments for handpieces -- 7. Dental dam instruments -- 8. Amalgam restorative instruments -- 9. Composite restorative instruments -- 10. Crown and bridge restorative instruments -- 11. Endodontic instruments -- 12. Hygiene instruments -- 13. Preventive and sealant instruments and bleaching trays -- 14. Orthodontic instruments -- 15. Universal surgical instruments -- 16. Periodontal instruments and periodontal surgical instruments -- 17. Oral surgery extraction instruments -- 18. Sterilization equipment -- 19. Dental materials equipment -- 20. Dental radiography equipment -- Index.
Keywords: Dental instruments and apparatus -- Handbooks, manuals, etc; Dental Instruments